Promoting EFL Students' Engagement by Using Bamboozle: Digital Game-Based Learning in Indonesian Higher Education - Aeni, Nur; Nur, Sahril; Limbong, Sunarlia; Yunus, Muhammad (Journal of English Education and Teaching, 2024)
Digital Game-based learning has been investigated to find the effective teaching strategy and media. However, little empirical evidence addresses how Bamboozle, a web-based game app, promotes language learners' behavioral, affective, social, and cognitive engagement. This study utilized an exploratory case study; seventy-eight EFL students participated in a gamified online course using Bamboozle. They were selected by cluster random sampling technique. This study revealed that the participants were engaged and actively involved in the teaching and learning process. In addition, it is found that students' engagement increased and they were motivated to learn interactive speaking. As the results showed that the students enjoyed the learning process, they were motivated. The students were involved in active participation and discussions. In addition, they were active in collaborative projects. According to the findings, the majority of students have a good opinion of the concept of Bamboozle as a game-based application. The participants were posted in three categories, namely: the highly engaged, the moderately engaged, and the lowly engaged. The higher they engage the better performance that they have in learning English, especially Interactive speaking. The findings suggest the utilization of digital game-based in EFL classrooms should focus more on critical thinking and problem-solving techniques. The implication extends to the broader context of EFL education in a higher learning context, highlighting the integration of Bamboozle as a game-based application to enhance the student’s motivation, and engagement and help to more easily understand the lesson.